Investigate a Gas Well Performance Using Nodal Analysis - Ben Mahmud, Hisham; Abdullah, A. (IOP Publishing, 2017)
Gas condensate well has unique reservoir characteristics and ups and downs in well behaviour affect the production rate significantly. A proper optimization can reduce the operating cost, maximize the hydrocarbon recovery and increase the net present value. Well level optimization can be achieved through optimizing well parameters, such as wellhead, tubing size, and skin factor. All of these factors have been investigated using a real field of Thrace Basin and PROSPER simulation program. The history matching data are validated to identify the future performance prediction for the same reservoir deliverability following the period changes. Therefore, predicted results are compared and validated with measured field data to provide the best production practices. Moreover, the results show that the skin factor has a large influence on the production rate by 45% reduction. The reduction in the reservoir pressure declines the production rate dramatically resulted in 70% decline. While manipulating the wellhead pressure shows minor decline compare to tubing size that does not show any significant change to production rate.